Study on the organ distribution of gold nanoparticles synthesized by γ-irradiation using carboxymethyl chitosan stabilizer after intravenous administration in mice - Phuong Linh, Do Thi; Nghia, Nguyen Trong; Luan, Le Quang (Vietnam Journal of Biotechnology, 2018)
Gold nanoparticles (AuNPs) with an average particle size of about 7 nm and concentration of 1 mM were synthesized by gamma rays irradiation method using 0.5% carboxymethyl chitosan (CMC) as a stabilizer. The characteristics of AuNPs were verified using UV-vis spectrum and TEM (Transmission Electron Microscope) images. The synthesized AuNPs were intravenously injected into tail of mice with a dose of 1 mg AuNPs per mouse for investigation of the in vivo distribution of AuNPs at different times. The analytical results showed that there was no significant difference in the blood haematological and serum biochemical indexes between the mice administrated with AuNPs and the control group. The gold content in the samples determined by k0-neutron activation analysis (k0-NAA) method indicated that after injection 1 h, AuNPs were mainly accumulated in liver (64.92%), blood (31.33%) and a small amount in lungs (2.16%) and kidneys (1.60%). After 6 hrs post-injection, the content of AuNPs was almost not determined in the blood, but its accumulation was increased in livers with 88.85%, lungs with 8.55% and kidneys with 2.10%. After 12 hrs of intravenous administration, the content of AuNPs was found to be slightly reduced by 83.86% in liver, but it was almost unchanged in lungs and kidneys. The results obtained in this study clearly indicated the distribution and the retention time of AuNPs in the mice. The AuNPs synthetized by gamma rays irradiation may potentially be developed for application as an X-ray contrast agent in diagnosis and as antioxidant agent for liver protection.